2013
DOI: 10.1111/mmi.12132
|View full text |Cite
|
Sign up to set email alerts
|

Quorum‐sensing regulation of a capsular polysaccharide receptor for the Rhodobacter capsulatus gene transfer agent (RcGTA)

Abstract: The gene transfer agent produced by Rhodobacter capsulatus (RcGTA) resembles a small tailed bacteri-ophage that packages almost random genomic DNA segments that may be transferred to other R. capsula-tus cells. Gene transfer agents are produced by a number of prokaryotes; however, no receptors have been identified. We investigated the RcGTA recipient capability of wild-type R. capsulatus cells at different culture growth phases, and found that the frequency of RcGTA-dependent acquisition of an allele increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
98
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(110 citation statements)
references
References 64 publications
2
98
0
Order By: Relevance
“…Two recent reports indicated that RcGTA is produced by a subset of the bacterial population and that the fraction of RcGTA gene-expressing cells in the total cell population is increased in an RcGTA overproducer strain, DE442 (14,20). Additionally, maximal gene transduction is dependent on the growth phase of recipient cultures, largely due to quorum-sensing regulation of the production of a capsule receptor needed for binding of RcGTA (21). The production of RcGTA is induced as cultures enter the stationary phase and particles are released through cell lysis (19,20), which requires the endolysin encoded by rcc00555 (14).…”
mentioning
confidence: 99%
“…Two recent reports indicated that RcGTA is produced by a subset of the bacterial population and that the fraction of RcGTA gene-expressing cells in the total cell population is increased in an RcGTA overproducer strain, DE442 (14,20). Additionally, maximal gene transduction is dependent on the growth phase of recipient cultures, largely due to quorum-sensing regulation of the production of a capsule receptor needed for binding of RcGTA (21). The production of RcGTA is induced as cultures enter the stationary phase and particles are released through cell lysis (19,20), which requires the endolysin encoded by rcc00555 (14).…”
mentioning
confidence: 99%
“…S3 and Table S1 in the supplemental material). This PCR product was digested with SphI and cloned into suicide plasmid pZDJ (27). The resultant plasmid was used as the template for a PCR with primers del_lexA_F and del_l-exA_R (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The ⌬280pG::lacZ mutant strain used for transposon Tn5 mutagenesis (31) was created by PCR amplifying the RcGTA promoter region as described previously (32) and subcloning it into SacI/BamHI double-digested suicide plasmid pZDJ (27), resulting in pZDJ::pGTA. The lacZ gene was PCR amplified from plasmid pXCA601 (33) with primers lacZ_F_BamHI and lacZ_R_HindIII (see Table S1 in the supplemental material), and the resulting fragment was digested with BamHI and HindIII and subcloned into BamHI/HindIII double-digested plasmid pBluescript, resulting in pBS-lacZ.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, GTAs are not inducible by mitomycin C (Marrs, 1974) and do not form plaques (Solioz and Marrs, 1977). The expression of GTA genes studied to date is controlled by cellular regulatory systems (Brimacombe et al, 2013;Schaefer et al, 2002) and functions as truly gene transfer agents for the host cells. GTAs play a role in lateral gene transfer in nature and, thus, affect the evolution of prokaryotic genomes.…”
Section: Introductionmentioning
confidence: 99%